Arché : a collection of patristic studies - Winden, J. C. M. van. (Vigiliae Christianae, Supplements, 1997)
During the past forty years J.C.M. van Winden OFM, Emeritus Professor of Early Christian Literature at Leiden University and editor of Vigiliae Christianae , has built up an impressive body of published research on early Christian thought and related areas of Greek and Jewish philosophy. In this volume in honour of his 75th birthday his more important contributions, originally published in a wide range of journals and other publications, have been collected together. These are grouped together in five categories: The archè in early christian thought, Essays on the Church Fathers, Philonica, Plotiniana, Essays on the relation between Greek and Patristic Thought. The volume includes a hitherto unpublished survey article on early Christian exegesis of 'the beginning' in Gen. 1:1 (in German), English translations of five contributions originally published in Dutch, and a complete bibliography of Pater van Winden's scholarly work.